Zygmunta Baumana myśli o ciele i zdrowiu – w kontekście edukacji do/dla/w starości - Kowalski, Mirosław (Adult Education Discourses, 2020)
Many researchers point to the fact that body/health is interpreted on at least two levels. The first one relates to human declarations and commitments, while the second relates to the value actually realized. They indicate that health (e.g. socio-mental) is the greatest treasure of immeasurable value in human life, and at the same time actively diminishes its weight, in favor of other, subjective values. It often turns out that, for example, physical health only becomes a significant value when it is lost or when a disease appears that hinders proper functioning and the achievement of life goals. Body and health are the categories underlying lifelong education, a specific problem/issue in the field of education for old age (care and medical staff), to old age (the whole society), through old age (from the youngest generation) and education in old age (older people). The article attempts to define the contemporary framework of discourses about the body and health, as well as the directions of theoretical analyses (contexts) and to outline practical references in the areas of the mentioned forms of education.